EXPERIMENTS SIMULATING SURFACE DEFORMATION INDUCED BY PLUTON EMPLACEMENT - Acocella V.; Mulugeta G. (My University, 2002)
We present centrifuge experiments to study the surface deformation induced by shallow pluton emplacement in a rheologically stratified crust. Sand simulates the topmost brittle crust; plastilina and denser silicone represent more and less competent crustal portions, respectively; lighter silicone simulates a buoyant intrusion. In the models, density differences affect the rate of intrusion but not their evolution or shape, whereas viscosity and strength stratifications control both the shape and rate of the intrusions. With a higher viscosity contrast (102-4) between the intrusion and the embedding media, the rise of the lighter silicone induces a laccolith-like intrusion, responsible for doming and thinning of the overburden; an apical depression may form, inducing silicone extrusion. Conversely, with a lower (101) viscosity contrast, the overburden and the intrusion exhibit a lens-shaped form, with a broad central depression bordered by an upward flexure towards the periphery. A sag in the floor of the intrusion is commonly observed; no silicone extrusion occurred. The intrusion is a hybrid between a laccolith and a lopolith. The comparison with nature (1) confirms roof uplift as an important means of accommodating space during pluton emplacement and (2) suggests that, where roof uplift plays a major role, pluton emplacement can induce a well-correlated sequence of events at surface: doming, the development of a depression and extrusion.
Keywords: PLUTON EMPLACEMENT; SURFACE DEFORMATION; ANALOGUE MODELLING